Method Development for Analysis of Cyclodextrin Inclusion Complexes with HPLC - Jajang Japar Sodik; Rusi Rismawanti (International Journal of Health and Medicine, 2024)
Cyclodextrin inclusion complexes have been widely used in the pharmaceutical industry to improve drug solubility and bioavailability. Analysis of these complexes using HPLC requires the development of appropriate and validated methods. To analyze and compare various HPLC methods used for the analysis of cyclodextrin inclusion complexes, and to identify challenges and trends in method development. A literature review was conducted of articles published in the last 10 years, focusing on HPLC methods for the analysis of cyclodextrin inclusion complexes. Parameters compared included column type, mobile phase composition, flow rate, and detection method. The majority of studies used C18 columns with varying lengths and particle sizes. The composition of the mobile phase varied, reflecting the diversity of properties of the complexes analyzed. The flow rate was generally 1.0 mL/min, with the exception of the HPLC/MS method. Detection methods included UV-Vis, PDA, fluorescence, and mass spectrometry. The main challenges included the dynamic equilibrium of the complexes and stability during analysis HPLC method development for the analysis of cyclodextrin inclusion complexes requires optimization of various parameters to overcome specific challenges. Future trends are towards the use of advanced technologies such as UHPLC and high-resolution mass detection.